2017
DOI: 10.3126/jcmc.v5i3.16525
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pterygium in a tertiary hospital in North-Western Nigeria

Abstract: Pterygium is a wing shaped conjunctival growth that encroaches onto the cornea. It was initially believed to be a conjunctival degeneration arising from pinquecula. However, it is now believed to be an active invasive inflammatory process leading to fibrovascular proliferation. The ocular symptoms of pterygium includes: tearing, redness, foreign body sensation and blurring of vision. Treatment option includes use of steroid and non-steroidal anti-inflammatory drug and various surgical options. A retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…[13][14][15] This may be attributable to prolonged exposure to risk factors associated with pterygium in older individuals. 16 Our study showed that the number of male patients was almost twice that of females similar to other studies. 15,[17][18][19][20] This could be explained by the fact that males tend to engage in more outdoor activities compared to females.…”
Section: Discussionsupporting
confidence: 90%
“…[13][14][15] This may be attributable to prolonged exposure to risk factors associated with pterygium in older individuals. 16 Our study showed that the number of male patients was almost twice that of females similar to other studies. 15,[17][18][19][20] This could be explained by the fact that males tend to engage in more outdoor activities compared to females.…”
Section: Discussionsupporting
confidence: 90%
“…Amongst the documented indications for surgical treatment are reduction in vision especially advanced pterygium that has covered the visual axis and cosmetic/unacceptable appearance of the eye. 7 The recurrence rate of pterygium after excision is high (30-50%). 8 The high recurrence rates are associated with different surgical techniques.…”
Section: Introductionmentioning
confidence: 99%